Well-Posedness of the Dirichlet and Poincaré Problems for the Wave Equation in a Many-Dimensional Domain - Aldashev, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We determine a many-dimensional domain in which the Dirichlet and Poincaré problems for the wave equation are uniquely solvable.